Characterization of intestinal gene expression profiles in Crohn's disease by genome-wide microarray analysis - Noble, Colin L.; Abbas, Alexander R.; Lees, Charles W.; Cornelius, Jennine; Toy, Karen; Modrusan, Zora; Clark, Hilary F.; Arnott, Ian D.; Penman, Ian D.; Satsangi, Jack; Diehl, Lauri (Inflammatory bowel diseases, 2010)
BackgroundGenome-wide microarray expression analysis creates a comprehensive picture of gene expression at the cellular level. The aim of this study was to investigate differential intestinal gene expression in patients with Crohn's disease (CD) and controls with subanalysis of confirmed CD susceptibility genes, associated pathways, and cell lineage.MethodsIn all, 172 biopsies from 53 CD and 31 control subjects were studied. Paired endoscopic biopsies were taken at ileocolonoscopy from five specific anatomical locations including the terminal ileum (TI) for RNA extraction and histology. The 41,058 expression sequence tags were analyzed using the Agilent platform.ResultsAnalysis of all CD biopsies versus controls showed 259 sequences were upregulated and 87 sequences were downregulated. Upregulated genes in CD included SAA1 (fold change [FC] +7.5, P = 1.47 × 10−41) and REGL (FC +7.3, P = 2.3 × 10−16), whereas cellular detoxification genes including-SLC14A2 (FC-2.49, P = 0.00002) were downregulated. In the CD TI biopsies diubiquitin (FC+11.3, P < 1 × 10−45), MMP3 (FC+7.4, P = 1.3 × 10−11), and IRTA1 (FC-11.4, P = 4.7 × 10−12) were differentially expressed compared to controls. In the colon SAA1 (FC+6.3, P = 5.3 × 10−8) was upregulated and thymic stromal lymphopoietin (TSLP) (FC-2.3, P = 2.7 × 10−6) was downregulated comparing noninflamed CD and control biopsies, and the colonic inflammatory CD signature was characterized by downregulation of the organic solute carriers-SLC38A4, SLC26A2, and OST alpha. Of CD susceptibility genes identified by genome-wide association scan IL-23A, JAK2, and STAT3 were upregulated in the CD group, confirming the dysregulation of Th17 signaling.ConclusionsThese data characterize the dysregulation of a series of specific inflammatory pathways highlighting potential pathogenic mechanisms as well as areas for translation to therapeutic targets. (Inflamm Bowel Dis 2010)